Regional Government Policy in the Implementation of Child-Friendly City: An Analysis of Way Kanan District - Prasetyawati, Suryati Endang; Fauzan, Muhammad; Amalia, Syarafina Dyah (Jurnal Dinamika Hukum, 2024)
The child-friendly city concept implementation in Way Kanan City is intended to fulfill the needs of children's rights there. This paper aims to contribute to policymakers’ implementation of child-friendly cities, especially in developing countries, by analyzing how child-friendly cities are implemented and the challenges faced. This article was created using socio-legal research methods. The results of this study show that the implementation is carried out by the Office of Women's Empowerment and Child Protection through several stages, namely, KLA development planning in the form of preparing Regional Action Plans, then implementing KLA development in the form of KLA programs’ implementation by involving all resources and implementing child-friendly school programs as well as monitoring and evaluating KLA development regularly. Implementation constraints come from internal factors. Challenges include limited human resources and an inability to understand women's empowerment and child protection issues, which affect socialization. Public facilities also need improvement to meet child-friendly standards. Meanwhile, technical coordination issues and misunderstandings about the KLA program's purpose arise due to external factors. Societal attitudes towards violence as education hinder program implementation. The suggestion for this research is to improve coordination between stakeholders or increase cooperation with partners to overcome problems regarding the lack of human resources, increase the budget and optimize the implementation of child-friendly city efforts.